PELAKSANAAN KAWIN HAMIL PADA MASYARAKAT ADAT DI DESA TANJUNG KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR - WIDYA KURNIA SARI (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Article 53 Compilation of Islamic Law has stated that, a woman who became pregnant out of wedlock who can legally married to the man who impregnated her without waiting for the birth of a child in her womb. The marriage continues to be valid and effective unless there is a divorce, so the marriage was performed not need to be restarted even after the birth of her child.The reality of the indigenous communities in the village of Tanjung District Koto Kampar Hulu Districts Kampar still upholds the customary law in force in this village. Marriage to a pregnant woman before getting marriage was forbidden, but to cover up the embarrassment should be expedited marriage (forced marriage), the consequences under customary law marriage is invalid. Legal marriage when repeated after forty days the baby is born.Keyword: Implementation - Married Pregnant - Customary Law - Village of Tanjung